1977
DOI: 10.1037/0278-7393.3.6.660
|View full text |Cite
|
Sign up to set email alerts
|

Similarity as distance: A structural principle for semantic memory.

Abstract: A review of some recent experiments suggested that general similarity between words might successfully function as a structural principle for semantic memory. A spatial model based on that assumption is proposed. Reaction times were taken as 16 observers judged which of two words was more similar to a third word. The results, which are consistent for two different categories of words and for two different methods of collecting similarity data, show that the Weber-Fechner effect exists for discriminations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 41 publications
5
42
0
Order By: Relevance
“…We agree with Hutchinson and Lockhead (1977) that a spati*l representat ion provides a rather general form of representation for a variety of purposes, and with Hollan Smith, and Shoben (1975) have noted that the choice of representation serves a largely heuristic function, and in the present research, the spatial representation seems to have served this function reasonably well. Although we believe that subjects use a spatial representation in solving these problems, we also believe that other representations are available to subjects as they solve these (and other) problems , and that subjects make use of these alternative representations as needed.…”
Section: Discussionsupporting
confidence: 87%
“…We agree with Hutchinson and Lockhead (1977) that a spati*l representat ion provides a rather general form of representation for a variety of purposes, and with Hollan Smith, and Shoben (1975) have noted that the choice of representation serves a largely heuristic function, and in the present research, the spatial representation seems to have served this function reasonably well. Although we believe that subjects use a spatial representation in solving these problems, we also believe that other representations are available to subjects as they solve these (and other) problems , and that subjects make use of these alternative representations as needed.…”
Section: Discussionsupporting
confidence: 87%
“…Since ratio and least are better than subtractive distance as predictors of RT, some of the between-/within-category effect in Figure 2 may be explainable as a ratio or least distance effect. Such an interpretation would seem to fit nicely with the results of Hutchinson and Lockhead (1977), who found that decisions about which of two named animals was more similar to a third were faster when the comparison animals were from the same category as the reference animal than when they were from different categories. Nonetheless, part of the between-/within-category effect in Figure 2 must also be due to some unique property of within-category triplets, such as peripheral chips always representing the correct choice.…”
Section: Other Distance Measuressupporting
confidence: 79%
“…The evidence from the present experiments of the reversed direction of mapping between similarity and RT for the two types of response might also be taken as evidence for a dual-process theory. However, Krumhansl (1978) has recently shown how it may be possible to obtain this altered mapping by taking into account both the distance between and the density surrounding points in a multidimensional space (see, also, Hutchinson & Lockhead, 1977;Monahan & Lockhead, 1977). In effect, Krumhansl attempts to predict both "same" and "different" judgments from a representational medium based solely on psychological distance between nonidentical objects, and thus this model-although not intended as a process modelseems consistent with a single-process approach based on a concept of "discnrninability."…”
Section: Directionally Reversed Mappingsmentioning
confidence: 99%